Redescription of the larva of Gynacantha cylindrata Karsch (Insecta: Odonata: Aeshnidae) - Domenico, Marco Di; Dijkstra, Klaas-Douwe B.; Carchini, Gianmaria (Zootaxa, 2016)
The ultimate stadium larva of Gynacantha cylindrata Karsch, 1891 is described and illustrated based on fifteen male and female exuviae from Bundibugyo, Uganda. The larva resembles those of the few described African species of the genus but shows a denser coverage of spine-like setae on body surface and abundance of hair-like setae on mouthparts. The female gonapophyses appear to be the longest described in the genus up to now and similar to those of G. villosa, a species included in the same group of African species.